P148 Impact of patient support programs on outcomes among patients with severe asthma treated with biologic therapies – a systematic literature review. (11th November 2022) - Rabe, APJ; Loke, WJ; Kielar, D; Morris, T; Shih, VH; Olinger, L; Musat, MG; Harricharan, S; Majeed, A; Heaney, L
Abstract : The optimal effectiveness of treatment in severe asthma (SA) is dependent on adherence to both inhaled and biologic medications. Patient support programs (PSPs) benefit patients with chronic diseases treated with biologics, such as rheumatic or inflammatory bowel diseases, but PSPs impact on outcomes in SA patients treated with biologics is unclear. We conducted a systematic literature review (SLR) to understand the impact of PSPs on treatment adherence, health-related quality of life (HRQOL), and asthma control in this population. Embase, Medline, and Cochrane databases were searched for studies published from 2003 (the year of the first biologic approval for SA) to March 2022 that described patient-support activities outside of routine clinical care for SA patients on biologic treatment. Nineteen records covering 15 studies were selected. Most studies described patient education programs (4/15) or support transitioning to at-home administration (7/15). Only 4 studies investigated the changes in patients' asthma treatment adherence, asthma control, or HRQOL, after participation in a PSP. In a UK-based study involving patients initiating biologic therapies, poor adherence to inhaled medication was related to patients' perception that they do not require it as their asthma is under control. Their adherence to inhaled therapy improved after participation in education sessions. Patient education on the importance of adherence to asthma treatments improved asthma control and HRQOL and significantly reduced the number of emergency room visits in a South American study. Multidisciplinary management involving therapeutic education and referrals to a dietitian, psychologist, tobacco addiction specialist, or social worker improved asthma control in patients with uncontrolled SA, according to a French study. A telemedicine-based PSP dedicated to assisting at-home biologic administration in children 6 years or older with SA in the UK, received positive feedback from caregivers and patients. Clinical parameters and asthma control did not deteriorate with at-home administration and HRQOL improved significantly over the first 3 months of at-home administration. All studies investigating the effects of PSPs among SA patients treated with biologics showed benefits in disease control and HRQOL. Training and telemedicine support were important for transitioning to at-home administration and monitoring per positive feedback from both patients and caregivers. Please refer to page A214 for declarations of interest related to this abstract.